PENGGUNAAN KOMPOSIT KARET ALAM-ARANG AKTIF-PASIR COR UNTUK MENGURANGI KANDUNGAN NITRAT DALAM LARUTANNYA - Dyah Ayu Anggraini; Tengku Ariful Amri; Amilia Linggawati (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Composite is a material made up of two parts, binder (matrix) and filler. This material is widely used in human activities as water purification media. Composite materials that used in this study consist of natural rubber as a matrix with filled activated charcoal and sand cast. The composition of the composite is 0% sand : 100% charcoal (KA), 50% sand : 50% charcoal (KAP), 100% sand : 0% charcoal (KP). These composites are used to reduce the nitrate content in the nitrate solution which have initial concentration of 5 and 10 ppm. Nitrate contents before and after passing the composite were analyzed using Brusin sulfate method. The results showed that the composite rail is more effective at reducing nitrate solution which has initial concentration of 10 ppm at 30o C. In these conditions the composite KA can reduce the high nitrate content to 73.38%, while the KAP and KP can only reduce nitrate content of 69.75% and 53.88% respectively.